BARRIER DESIGN STRATEGIES TO CONTROL NOISE INGRESS INTO DOMESTIC BUILDINGS - Christina E. Mediastika (DIMENSI (Journal of Architecture and Built Environment), 2003)
Noise source for buildings adjacent to streets is traffic-generated predominantly. Where people are mostly spend their time indoors, it is important for buildings to have screening or blocking to control noise intrusion into living spaces. But this blocking should also permit airflow. This is important for middle to low-cost domestic buildings, which do not employ conditioned ventilation. A common feature of Indonesian buildings, fence, is studied to perform noise barrier. The fence -a barrier to be- should obey three factors: position, dimension, and material. All these three factors were studied to seek compromised design for acoustic performance and natural ventilation purpose. Domestic building situated in the urban area of Yogyakarta was studying to see the most possible design of the barrier to be. There are two calculation methods employed to investigate the proposed design. The study shows that it is possible to gain minimum of 10 dB noise reduction by placing windows within the shadow effect of approximately 1.5 height fence-barrier.